PERUBAHAN ORGANISASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN HOTEL (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2022)
This study aims to provide empirical evidence of the effect of organizational change and compensation on the performance of hotel employees in Madiun City due to the Covid-19 pandemic. The sampling technique used in this study was a saturated sample with a total of 123 employees of five-star hotels in Madiun City. The research was conducted in a survey phase, distributing questionnaires and processing data. Data collection used primary data in the form of questionnaires which were distributed directly and processed using multiple linear regression method. while data processing used SPSS 24. The results of the study partially show that organizational change and compensation have a positive and significant effect on the performance of hotel employees in Madiun City. The results of the research simultaneously show that organizational changes and compensation simultaneously affect the performance of hotel employees in Madiun City